ChemInform Abstract: Ionic Liquids and Continuous Flow Processes: A Good Marriage to Design Sustainable Processes. Issue 29 (July 2015) - Garcia‐Verdugo, Eduardo; Altava, Belen; Burguete, M. Isabel; Lozano, Pedro; Luis, S. V.
Abstract Review: [111 refs.